Mechanical Analysis of Structural Damage Detection Device for Cylinder Tower. Issue 1 (1st January 2022) - Wang, Zhiyuan; Sun, Changle; Wang, Jian; Zhao, Kang; Liu, Tingrui
Abstract: Wind turbines suffer from severe weather and complex environment for a long time, so wind turbine towers can cause structural damage. As an important part of wind turbine, tower damage detection is particularly important. In this study, a structural damage detection device for cylinder tower is introduced and its mechanical analysis is carried out. Due to the special structure design of the device, it has the characteristics of comprehensive detection, accuracy and efficiency.